Kościoły klasztorne norbertanek w średniowiecznej Polsce w świetle reform monastycznych XI i XII w. - Sokołowski, Norbert (Jagiellonian University, 2019)
Theme of this thesis are churches of premonstratensians in medieval Poland shown in light of monastical reforms in 11th and 12th century. The purpose of this thesis is to connect medieval churches of premonstratensians in Poland: in Strzelno and in Kraków-Zwierzyniec with churches, which were built under influence of „Hirsau reform“. Thesis consists of 5 chapters. In the first one author presents in shortened form the beginning of premonstratensians, the female’s branch of this order and history of premonstratensians‘ beginning in Poland. In the second chapter author presents the state of research about churches in Strzelno, their history and description. In the third chapter author presents analogous informations about Saint Salvator‘s church in Kraków-Zwierzyniec. In the fourth chapter author presents the state of research and the history of Saint Augustine and John the Baptist church in Kraków-Zwierzyniec. In the fifth chapter author analyses similarities and differences between churches in Strzelno and Kraków and churches, mainly on german territories, which were built under influence of „Hirsau reform“.
Accepted: 2020-07-28T01:15:44Z
Keywords: 🇵🇱 poland (general)

Życiowe dokonania Cypriana – zakonnika i biskupa wrocławskiego w latach 1201–1207 - Jerzak, Norbert (Wrocławski Przegląd Teologiczny, 2019)
Keywords: 👤 cyprian of wrocław

Kilka uwag o historii klasztoru w Opolu-Czarnowasach - Sadowski, Piotr (Opolskie Studia Administracyjno-Prawne, 2019)
OCLC: 1242190039
Keywords: czarnowąsy

Krzyż i chwała : błogosławiona Bronisława i Konwent Panien Norbertanek na Zwierzyńcu w Krakowie = The cross and glory : blessed Bronislava and Norbertine Canonesses Convent in Zwierzyniec, Cracow - Stefaniak, Piotr (Księgarnia św. Jacka, 2019)
Keywords: zwierzyniec; 👤 bronislava of kamień